Culture in the Federal Republic of Germany : 1945 - 1995 - Pommerin, Reiner, 1943-2024 17.06.1943-04.07.2024 (German historical perspectives series;, 1996)
Postwar German culture - East and West - and the political implications of various cultural developments are the focus of this provocative study by some of Germany's leading cultural and intellectual historians. Many of the contributors - Hermann Glaser and Kurt Sontheimer, in particular - have played important roles in the development of cultural activities in the Federal Republic and offer an insider's perspective on the literature, architecture, performing arts, theatre and cinema of this tumultuous period